A dose ranging study of ibuprofen suspension as an antipyretic. Issue 9 (September 1991) - Marriott, S C; Stephenson, T J; Hull, D; Pownall, R; Smith, C M; Butler, A
Abstract : A double blind trial was conducted to determine the dose of ibuprofen suspension, which is effective in reducing the body temperature. The principal measure of efficacy was a reduction in axillary temperature of 1 degree C or more three hours after dosing. A second objective of the trial was to compare the incidence and severity of side effects and the palatability of a range of ibuprofen doses. Ninety three children were included in the analysis. All four doses of ibuprofen studied (0.625 mg/kg-5 mg/kg) were associated with temperature reduction and only the lowest dose failed to satisfy the principal measure of efficacy. The influence of dose on the magnitude of the body temperature reduction was significant and the 5 mg/kg dose achieved the largest mean reduction in body temperature (2 degrees C). The tolerability and palatability of all doses studied were excellent. These findings suggest that ibuprofen is a good alternative to paracetamol as an antipyretic.